Kerala's education system: from inclusion to exclusion? - Najith Kumar; George, K.K. (2009)
The paper examines the recent shifts in Kerala's education system from an inclusive to an exclusive one. The pendulum seems to be swinging from one extreme to the other, from a highly subsidised and a largely state-sponsored and state-supported system to a mostly self-financing system, a euphemism for a student-financed commercial system. This paper examines the economic, social and political forces that led to this shift, almost tectonic in scale. It also examines the long-term consequences of such a shift to Kerala's economy and society. - Reproduced.
Keywords: Educational systems - India - Kerala; Educational systems